Maintaining Ideology through Racial Distinction during the 1930s America in Ralph Ellison’s Invisible Man - Raisa Hani Tamara; Achmad Munjid (Universitas Sanata Dharma, 2022)
Racial issues in 1930s America illustrate the high racial tension between Whites and African-Americans due to the series of mass racial violence. Despite the rapid industrialization, African-Americans, in this period, struggled to find their equal place in society. Ralph Ellison’s Invisible Man depicts the social conditions of African-American workers’ socio-economic backwardness in the 1930s. This novel is set during the post-reconstruction era of America, where Jim Crow laws were instituted. Therefore, the analysis of racial distinction in this novel is conducted using Post-Nationalist American Studies and Marxism approach. Therefore, this qualitative research utilizes Althusser’s theories: of Ideology and Ideological State Apparatus (ISA). The findings show how White ideology is depicted and maintained: (1) the depiction of Ideology can be seen through the class distinction and racial dependency in which African-Americans are created to be inferior and submissive to White people. Then, (2) the maintenance of ideology relies on Althusser’s concept of Ideological State Apparatuses, such as religious, family, education, legal, politic, trade union, communication, and cultural institutions, function as an adjunct of the state that perpetuates and preserves White-centered values. Thus, the racially segregated society essentially only supports the needs of White capitalists as the ruling class.